A method for graphitizing amorphous carbon

By graphitizing amorphous carbon at low temperature using a metal alloy catalyst and removing impurities by acid washing, the problems of high graphitization temperature, high cost and difficult to remove impurities in the prior art are solved, and graphite material preparation with low cost and excellent electrochemical properties is achieved.

CN116040622BActive Publication Date: 2025-04-29EVE POWER CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211698739.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-28
Publication Date
2025-04-29
Estimated Expiration
2042-12-28

AI Technical Summary

Technical Problem

The graphitization temperature of the graphite anode materials of existing lithium-ion batteries is high, resulting in high cost and damaged material structural characteristics, and it is difficult to completely remove impurities introduced by the catalyst.

Method used

A metal alloy is used as a catalyst, and graphitization is carried out by mixing with amorphous carbon and graphitizing at a lower temperature, and then removing metal impurities through a pickling process to obtain a graphite material with high purity and good structural characteristics.

Benefits of technology

The graphitization temperature and cost are reduced, and the problems of introducing impurities and difficulty in removing at high temperatures are avoided. The obtained graphite material has excellent electrochemical properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116040622B_ABST
    Figure CN116040622B_ABST
Patent Text Reader

Abstract

The present invention provides a method for graphitizing amorphous carbon, the method comprising the following steps: mixing amorphous carbon and a metal alloy, then heating and graphitizing to obtain a graphitized material; the metal alloy comprises at least two metals; and pickling the graphitized material to obtain a graphite material. The method of the present invention can reduce the graphitization temperature of amorphous carbon, and does not need to increase the temperature to above 2000°C for impurity removal, so the cost can be further reduced. Meanwhile, the impurities after graphitization by the method are mainly metal elements, which can be removed by a low-cost pickling process, with good impurity removal effect, without introducing other impurity elements that are difficult to remove, and the obtained graphite material can retain the original structural characteristics of the carbon material to the greatest extent and has excellent electrochemical properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of battery materials and relates to a method for graphitizing amorphous carbon. Background Art

[0002] The existing commercialized graphite negative electrode materials for lithium-ion batteries are generally obtained by graphitizing amorphous carbon, but the current graphitization temperature is generally above 2500°C. Compared with the carbonization process below 2000°C, the high temperature time is long and the cost is higher. For example, CN 113086979A discloses a preparation method of graphite material, graphite material and application, and negative electrode material for lithium-ion batteries. The disclosed preparation method includes the following steps: graphitizing the raw coke to obtain the graphite material, wherein the graphitization temperature is 2800-3200°C and the holding time is 1-6h. The disclosed preparation method has a high graphitization temperature and high cost. At the same time, high-temperature graphitization will cause the carbon material to be highly lattice-formed, causing the carbon particle size to increase, causing the pore structure in the carbon material to be severely damaged, causing the specific surface area to drop sharply, and destroying the original structural characteristics of the carbon material; therefore, reducing the graphitization temperature is an effective measure to reduce the cost of the graphitization process and improve the performance of the graphite material.

[0003] Low-temperature graphitization can retain the original structural characteristics of carbon materials to the greatest extent, while improving the conductivity of carbon materials and optimizing their pore structure and surface properties; among them, catalytic graphitization is an effective measure to reduce the graphitization temperature. Catalytic graphitization refers to the introduction of catalysts into the formula to achieve graphitization at a lower temperature, or to increase the degree of graphitization under the same temperature conditions. In the prior art, iron or ferrosilicon is often used as a catalyst for low-temperature graphitization of amorphous carbon. Since the melting points of iron and ferrosilicon are 1538°C and 1250°C respectively, the catalytic effect begins to occur at this temperature. When the temperature is raised to 2000°C, iron escapes in the form of steam, and when the temperature is raised to 2240°C, silicon escapes in the form of steam. Therefore, the catalyst can achieve the purpose of low-temperature graphitization without residual impurities. However, the iron and ferrosilicon catalytic graphitization process can be divided into two parts according to the temperature change. The first part is catalysis, and the corresponding temperature is below 2000°C and above the melting point of the catalyst; the second part is impurity removal, that is, the temperature is raised to 2000°C-2240°C to remove iron and silicon. Although the graphitization temperature is reduced, the impurity removal temperature is as high as above 2000°C, and the silicon impurities generated during the catalytic process are difficult to remove.

[0004] Based on the above research, it is necessary to provide a method for graphitizing amorphous carbon, which can complete graphitization at low temperature, has low cost, does not introduce other impurities, and the impurity removal process is not only simple and effective, but also the obtained graphite material has excellent electrochemical properties. Summary of the invention

[0005] The object of the present invention is to provide a method for graphitizing amorphous carbon, and in particular to a method for low-temperature graphitization of amorphous carbon. The method has low cost and does not need to be carried out at a high temperature of more than 2000°C. The obtained graphite material can retain the original structural characteristics and has excellent electrochemical properties. At the same time, the method will not introduce other impurities and has a good impurity removal effect.

[0006] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:

[0007] The present invention provides a method for graphitizing amorphous carbon, the method comprising the following steps:

[0008] (1) mixing amorphous carbon and a metal alloy, and then heating to graphitize to obtain a graphitized material;

[0009] The metal alloy includes at least two metals;

[0010] (2) acid-washing the graphitized material in step (1) to obtain a graphite material.

[0011] The present invention adopts a metal alloy as a catalyst, which can not only reduce the temperature of graphitization of amorphous carbon, but also does not produce impurities such as silicon. The cost is low, and there is no need to increase the temperature again to remove the catalyst. The metal impurities can be removed through a pickling process. The obtained graphite material has high purity, can retain the original structural characteristics of the carbon material to the greatest extent, improve the conductivity of the material, and can optimize its pore structure and surface properties. The performance of the material is equivalent to or even improved after high-temperature graphitization.

[0012] Preferably, the melting point of the metal alloy in step (1) is less than 1538°C, for example, it can be 1530°C, 1500°C, 1450°C or 1400°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are still applicable.

[0013] Preferably, the metal alloy in step (1) comprises an iron-nickel metal alloy.

[0014] The metal alloy used in the present invention has a suitable melting point, can successfully graphitize amorphous carbon, and is easy to remove without introducing other impurities.

[0015] Preferably, in the iron-nickel metal alloy, the nickel content is 20-60wt%, for example, 20wt%, 30wt%, 40wt%, 50wt% or 60wt%, but is not limited to the listed values, and other unlisted values ​​within the numerical range are still applicable.

[0016] In the alloy of the present invention, the contents of the two metals should be within a reasonable range, because the melting point of the alloy shows a trend of first decreasing and then increasing with the increase of the nickel content. If the nickel content is too high, the melting point will be too high. If the nickel content is too low, the melting point will also be too high. That is, a high or low nickel content will affect the graphitization effect.

[0017] Preferably, in the amorphous carbon and metal alloy in step (1), the content of the metal alloy is 10-30wt%, for example, it can be 10wt%, 15wt%, 20wt%, 25wt% or 30wt%, but is not limited to the listed values, and other unlisted values ​​within the numerical range are still applicable.

[0018] The metal alloy added in the present invention needs to be within a reasonable range to effectively reduce the graphitization temperature and effectively graphitize the amorphous carbon. If the added content of the metal alloy is too low, the yield and graphite quality will be seriously affected. If the added content of the metal alloy is too high, it will cause unnecessary waste in cost and will also affect the pickling effect to a certain extent.

[0019] Preferably, the graphitization temperature in step (1) is 1400-1600°C, for example, 1400°C, 1450°C, 1500°C, 1550°C or 1600°C, but is not limited to the listed values, and other values ​​not listed within the numerical range are still applicable.

[0020] Preferably, the graphitization time in step (1) is 24-72 h, for example, 24 h, 30 h, 35 h, 40 h, 45 h, 50 h, 55 h, 60 h, 65 h, 70 h or 72 h, but is not limited to the listed values, and other values ​​not listed within the numerical range are still applicable.

[0021] Preferably, the graphitization in step (1) is carried out under a protective gas.

[0022] Preferably, the protective gas includes any one of nitrogen, argon, helium or krypton, or a combination of at least two of them. Typical but non-limiting combinations include a combination of nitrogen and argon, or a combination of helium and krypton.

[0023] Preferably, the pH of the pickling solution used in the pickling in step (2) is 0-7, but does not include 0 and 7. For example, it can be 0.1, 1, 2, 3, 4, 5, 6 or 6.5, but is not limited to the listed values. Other unlisted values ​​within the numerical range are still applicable.

[0024] Preferably, the pickling solution comprises any one of nitric acid, hydrochloric acid or hydrofluoric acid, or a combination of at least two of them.

[0025] Preferably, the acid washing in step (2) is followed by washing with distilled water.

[0026] Preferably, the washing with distilled water is followed by drying.

[0027] Preferably, the drying temperature is 110-130°C, for example, 110°C, 115°C, 120°C, 125°C or 130°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are still applicable.

[0028] Preferably, the drying time is 10-14 hours, for example, 10 hours, 11 hours, 12 hours, 13 hours or 14 hours, but is not limited to the listed values, and other unlisted values ​​within the numerical range are still applicable.

[0029] As a preferred technical solution of the present invention, the method comprises the following steps:

[0030] (1) mixing amorphous carbon and an iron-nickel metal alloy, and then graphitizing them in a protective gas at a temperature of 1400-1600° C. for 24-72 hours to obtain a graphitized material;

[0031] In the iron-nickel metal alloy, the content of nickel is 20-60wt%; in the amorphous carbon and iron-nickel metal alloy, the content of the iron-nickel metal alloy is 10-30wt%;

[0032] (2) The graphitized material in step (1) is pickled with an acid wash solution, then washed with distilled water, and then dried at a temperature of 110-130° C. for 10-14 hours to obtain a graphite material;

[0033] The pH of the pickling solution is 0-7, but excluding 0 and 7. The pickling solution includes any one of nitric acid, hydrochloric acid or hydrofluoric acid, or a combination of at least two of them.

[0034] Compared with the prior art, the present invention has the following beneficial effects:

[0035] The present invention adopts a metal alloy as a catalyst, and can reduce the temperature of graphitization of amorphous carbon to within 1400-1600°C. Not only does it not need to be effectively graphitized at high temperature, which reduces the cost, but it also does not need to increase the temperature to 2000-2240°C for impurity removal, and the cost can be further reduced. At the same time, the impurities after graphitization in the method of the present invention are mainly metal elements, which can be removed by a low-cost pickling process, with a good impurity removal effect, without introducing other impurity elements that are difficult to remove, and the obtained graphite material can retain the original structural characteristics of the carbon material to the greatest extent, and has excellent electrochemical properties. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 This is a preparation flow chart of the method described in Example 1 of the present invention;

[0037] Figure 2 The graph is a cycle performance diagram of batteries prepared using the graphite materials obtained in Example 1 of the present invention and Comparative Example 1. DETAILED DESCRIPTION

[0038] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0039] Example 1

[0040] This embodiment provides a method for graphitizing amorphous carbon. The flow chart of the method is as follows: Figure 1 As shown, the method comprises the following steps:

[0041] (1) mixing amorphous carbon and an iron-nickel metal alloy, and then graphitizing them in an argon gas at a temperature of 1600° C. for 48 hours to obtain a graphitized material;

[0042] In the iron-nickel metal alloy, the content of nickel is 60wt%; in the amorphous carbon and iron-nickel metal alloy, the content of the iron-nickel metal alloy is 20wt%;

[0043] (2) The graphitized material in step (1) is pickled with an acid wash solution, then washed with distilled water, and then dried at 120° C. for 12 h to obtain a graphite material;

[0044] The pickling solution is nitric acid with a pH of 3;

[0045] The cycle performance of the graphite material obtained in this example after being prepared into a battery is shown in the figure below: Figure 2 shown.

[0046] Example 2

[0047] This embodiment provides a method for graphitizing amorphous carbon, the method comprising the following steps:

[0048] (1) mixing amorphous carbon and an iron-nickel metal alloy, and then graphitizing them in an argon gas at a temperature of 1500° C. for 24 hours to obtain a graphitized material;

[0049] In the iron-nickel metal alloy, the content of nickel is 20wt%; in the amorphous carbon and iron-nickel metal alloy, the content of the iron-nickel metal alloy is 30wt%;

[0050] (2) The graphitized material in step (1) is pickled with an acid wash solution, then washed with distilled water, and then dried at 130° C. for 10 h to obtain a graphite material;

[0051] The pickling solution is hydrofluoric acid with a pH of 6.

[0052] Example 3

[0053] This embodiment provides a method for graphitizing amorphous carbon, the method comprising the following steps:

[0054] (1) mixing amorphous carbon and an iron-nickel metal alloy, and then graphitizing them in a nitrogen gas at a temperature of 1400° C. for 72 hours to obtain a graphitized material;

[0055] In the iron-nickel metal alloy, the content of nickel is 40wt%; in the amorphous carbon and iron-nickel metal alloy, the content of the iron-nickel metal alloy is 10wt%;

[0056] (2) The graphitized material in step (1) is pickled with an acid wash solution, then washed with distilled water, and then dried at 110° C. for 14 h to obtain a graphite material;

[0057] The pickling solution is hydrochloric acid with a pH of 1.

[0058] Example 4

[0059] This embodiment provides a method for graphitizing amorphous carbon, which is the same as that of Embodiment 1 except that the nickel content in the iron-nickel metal alloy in step (1) is 10 wt %.

[0060] Example 5

[0061] This embodiment provides a method for graphitizing amorphous carbon, which is the same as that of Embodiment 1 except that the nickel content in the iron-nickel metal alloy in step (1) is 70 wt %.

[0062] Example 6

[0063] This embodiment provides a method for graphitizing amorphous carbon, which is the same as that of Embodiment 1 except that in step (1), the content of the iron-nickel metal alloy in the amorphous carbon and the iron-nickel metal alloy is 5 wt %.

[0064] Example 7

[0065] This embodiment provides a method for graphitizing amorphous carbon, which is the same as that of Embodiment 1 except that in step (1), the content of the iron-nickel metal alloy in the amorphous carbon and the iron-nickel metal alloy is 35 wt %.

[0066] Example 8

[0067] This embodiment provides a method for graphitizing amorphous carbon, which is the same as that of Embodiment 1 except that the graphitization temperature in step (1) is 1300°C.

[0068] Example 9

[0069] This embodiment provides a method for graphitizing amorphous carbon, which is the same as that of Embodiment 1 except that the graphitization temperature in step (1) is 1700°C.

[0070] Example 10

[0071] This embodiment provides a method for graphitizing amorphous carbon, which is the same as that of Embodiment 1 except that the iron-nickel metal alloy in step (1) further contains 10 wt % silicon.

[0072] Comparative Example 1

[0073] This comparative example provides a method for graphitizing amorphous carbon, the method comprising the following steps:

[0074] After graphitizing the amorphous carbon at a temperature of 2500°C for 48 hours, a graphite material is obtained;

[0075] The cycle performance of the graphite material obtained in this comparative example after being prepared into a battery is shown in the figure Figure 2 shown.

[0076] Comparative Example 2

[0077] This comparative example provides a method for graphitizing amorphous carbon, which is the same as Example 1 except that the mass of nickel in the iron-nickel metal alloy in step (1) is replaced by silicon.

[0078] Comparative Example 3

[0079] This comparative example provides a method for graphitizing amorphous carbon, which is the same as Example 1 except that in step (2), the graphitized material in step (1) is kept at 2000° C. for 3 h instead of acid washing.

[0080] The graphite materials obtained in the above embodiments and comparative examples are tested for the degree of graphitization. The testing method is as follows: XRD of the graphite materials is obtained by testing (by confirming d 002 , into the graphitization degree formula to calculate the graphitization degree), and Raman (confirm I D / I G Ratio, the smaller the ratio, the better the graphitization degree);

[0081] The graphite materials obtained in the above embodiments and comparative examples were prepared into negative electrode sheets. After batteries were formed with nickel cobalt lithium manganese oxide ternary positive electrodes, their cycle performance was tested under normal temperature and pressure and 1.5A / 3A charge and discharge conditions. The capacity retention rates after 500 and 1000 cycles are shown in Table 1.

[0082] Table 1

[0083]

[0084] From the above table we can see that:

[0085] (1) The method of the present invention can successfully reduce the graphitization temperature of amorphous carbon, not only the degree of graphitization is high, but also the performance of the obtained graphite material is not affected, and it has excellent electrochemical properties; it can be seen from Example 1 and Comparative Example 1 that Comparative Example 1 adopts a conventional high-temperature graphitization method, which has a relatively high cost; it can be seen from Example 1 and Comparative Example 2 that the present invention adopts a metal alloy as a catalyst, which can not only reduce the graphitization temperature but also be easy to remove, while the use of ferrosilicon alloy as a catalyst makes it difficult to remove the generated silicon, so the performance of the obtained graphite material is reduced; it can be seen from Example 1 and Comparative Example 3 that the pickling impurity removal process of the present invention can not only reduce the cost of graphite material preparation, but also has a high impurity removal effect, and the obtained graphite material has excellent performance.

[0086] (2) It can be seen from Examples 1 and 4-5 that the proportion of alloy components will affect the degree of graphitization and the impurity removal process. The alloy components in the present invention can further improve the performance of the obtained graphite material within a reasonable range; from Examples 1 and 6-7, the amount of alloy added will also affect the effect of graphitization, thereby affecting the performance of the obtained graphite material; from Examples 1 and 8, it can be seen that when the graphitization temperature is too low, effective graphitization cannot be achieved. From Examples 1 and 9, it can be seen that increasing the graphitization temperature does not significantly improve the graphitization effect and will also increase energy consumption; from Examples 1 and 10, it can be seen that when the alloy contains silicon, impurities cannot be effectively removed, thereby affecting the performance of the obtained graphite material.

[0087] In summary, the present invention provides a method for graphitizing amorphous carbon, which has low cost and does not need to be carried out at a high temperature of more than 2000°C. The obtained graphite material can retain the original structural characteristics and has excellent electrochemical properties. At the same time, the method will not introduce other impurities and has a good impurity removal effect.

[0088] The above description is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention are within the protection scope and disclosure scope of the present invention.

Claims

1. A method for graphitizing amorphous carbon, characterized in that: The method comprises the following steps: (1) mixing amorphous carbon and a metal alloy, and then heating them to graphitize them to obtain a graphitized material; The metal alloy includes at least two metals; The graphitization temperature is 1400-1600°C; The metal alloy is an iron-nickel metal alloy, and the content of nickel in the iron-nickel metal alloy is 50-60wt%; In the amorphous carbon and the metal alloy, the content of the metal alloy is 20-25wt%; (2) acid-washing the graphitized material in step (1) to obtain a graphite material; The pH of the pickling solution used in the pickling is 3-6.

2. The method according to claim 1, characterized in that The melting point of the metal alloy in step (1) is less than 1538°C.

3. The method according to claim 1, characterized in that The graphitization time in step (1) is 24-72 hours.

4. The method according to claim 1, characterized in that: The graphitization in step (1) is carried out under a protective gas.

5. The method according to claim 1, characterized in that The pickling solution includes any one of nitric acid, hydrochloric acid or hydrofluoric acid, or a combination of at least two of them.

6. The method according to claim 1, characterized in that After the acid washing in step (2), the substrate is washed with distilled water.

7. The method according to claim 6, characterized in that The distilled water washing is followed by drying.

8. The method according to claim 7, characterized in that The drying temperature is 110-130°C.

9. The method according to claim 7, characterized in that: The drying time is 10-14 hours.

10. The method according to claim 1, characterized in that The method comprises the following steps: (1) mixing amorphous carbon and an iron-nickel metal alloy, and then graphitizing them in a protective gas at a temperature of 1400-1600° C. for 24-72 hours to obtain a graphitized material; In the iron-nickel metal alloy, the content of nickel is 50-60wt%; in the amorphous carbon and the iron-nickel metal alloy, the content of the iron-nickel metal alloy is 20-25wt%; (2) The graphitized material in step (1) is pickled with an acid solution, then washed with distilled water, and then dried at a temperature of 110-130° C. for 10-14 hours to obtain a graphite material; The pH of the pickling solution is 3-6, and the pickling solution includes any one of nitric acid, hydrochloric acid or hydrofluoric acid, or a combination of at least two of them.

Citation Information

Patent Citations

  • Preparation method of graphite material, graphite material, application of graphite material and lithium ion battery negative electrode material

    CN113086979A

  • Collaborative graphitization method for amorphous carbon material

    CN102745677A